Long-Term Clinical Outcomes of Patients Treated With Everolimus-Eluting Bioresorbable Stents in Routine Practice: 2-Year Results of the ISAR-ABSORB Registry - Wiebe, Jens; Hoppmann, Petra; Colleran, Roisin; Kufner, Sebastian; Valeskini, Michael; Cassese, Salvatore; Schneider, Simon; Joner, Michael; Schunkert, Heribert; Laugwitz, Karl-Ludwig; Kastrati, Adnan; Byrne, Robert A. (Jacc-Cardiovascular Interventions, 2017)
Objectives The aim of this study was to report clinical outcomes in patients treated in routine practice 2 years after everolimus-eluting bioresorbable stent (BRS) implantation. Background Long-term results in patients undergoing BRS implantation in routine clinical practice are sparse, and existing evidence from randomized trials considers mostly selected patients. Methods The ISAR-ABSORB registry enrolled consecutive patients undergoing BRS implantation in routine clinical practice at 2 high-volume centers in Germany. Angiographic follow-up was scheduled after 6 to 8 months and clinical follow-up to 24 months. The primary endpoint was the composite of death, myocardial infarction, or target lesion revascularization, and secondary endpoints included individual components of the primary endpoint and definite stent thrombosis. Event rates were calculated using the Kaplan-Meier method. Results A total of 419 patients were included. The mean age was 66.6 ± 10.9 years, 31.5% had diabetes, and 39.0% presented with acute coronary syndrome. Forty-nine percent of lesions were considered complex (American College of Cardiology/American Heart Association type B2 or C), and 13.1% were bifurcation lesions. The mean reference vessel diameter was 2.89 ± 0.46 mm. At 2 years, the primary endpoint had occurred in 21.6% of patients: death in 6.3%, myocardial infarction in 3.9%, target lesion revascularization in 16.0%, and definite stent thrombosis in 3.8%. Conclusions Long-term follow-up of patients treated with BRS in routine practice showed higher event rates than expected. Future studies are required to determine the impact of changes in implantation technique and to define the optimal duration of dual antiplatelet therapy in these patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: bioresorbable stent(s); clinical outcomes; percutaneous coronary intervention